Frequency of Factor V Leiden and Prothrombin Polymorphism in South of Iran - Javad Dehbozorgian (Iranian Journal of Medical Sciences, 2009)
Normal hemostasis requires balanced regulation of prothromboticand antithrombotic factors. Inherited alteration of factor Vand prothrombin gene, the G20210A mutation, increases the resistanceof factor V to degradation and booster production ofprothrombin respectively. These alterations can increase hypercoagulabilityleading to thrombotic consequences. We aimed toassess the frequencies of these mutations in a group of the populationof southern Iran. In total, 198 healthy volunteers with theage range of 1-64 years were selected and screened for factor VLeiden and prothrombin mutations using polymerase chain reactionand restriction fragment length polymorphism techniques.The carrier frequencies for factor V Leiden and prothrombin mutationin the studied cohort were 4.1% and 3.07%, respectively.In the studied area, the allele frequency of factor V ishigher than the prothrombin G20210A mutation (0.0204 v0.0153). According to the data and Hardy-Weinberger equation,the total risk of thrombosis caused by homozygosity andheterozygosity of factor V Leiden, prothrombin G20210A mutationand compound heterozygosity of these mutations areabout 1 in 500 individuals.